2010
DOI: 10.1039/c0cc01842b
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight gelator–dextran composites

Abstract: Incorporation of dextran into a hydrogel formed using a low molecular weight dipeptide-conjugate gelator results in controlled modification of the material properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 26 publications
2
60
0
Order By: Relevance
“…Increasing to 5 mg/mL fucoidan an increase in intensity at low Q was visible and a clear deviation from I α Q −1 scattering to a Q −1   15 . power law which we interpret to be due to dilute large aggregates in the hydrogel.…”
Section: Resultsmentioning
confidence: 94%
“…Increasing to 5 mg/mL fucoidan an increase in intensity at low Q was visible and a clear deviation from I α Q −1 scattering to a Q −1   15 . power law which we interpret to be due to dilute large aggregates in the hydrogel.…”
Section: Resultsmentioning
confidence: 94%
“…Smith et al prepared robust hybrid hydrogels via the assembly of a hydrogelator within polysaccharide hydrogel networks 21. Yang et al and Adams et al also showed that mixing supramolecular hydrogels with agarose and dextran leads to novel hybrid hydrogels with tunable mechanical strength 22,23. Recently, our group developed polymer enhanced hybrid self-recovering hydrogels via glucose oxidase mediated polymerization 24.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of amplification by electrostatic coassembly is likely not exclusive to saccharides. Indeed, significant cooperative effects have been observed in co-assembly of Fmoc-peptides with (charged) proteins 23 and it will be interesting to investigate the possibility of adaptive reconfiguration in response to protein templating. More…”
Section: Discussionmentioning
confidence: 99%
“…20,21 The properties of peptide nanostructures can be altered dramatically by co-assembly 22,23 with macromolecules where specific interactions (e.g. electrostatic, aromatic stacking) and templating 24 might be utilized to direct the assembly process.…”
Section: Introductionmentioning
confidence: 99%